ANALYSIS OF IDENTITY IN MY MOTYHER/MY SELF NOVEL - DJOKO ARDHITYAWAN; NI'MATUL BADRIYAH (Fakultas Sastra Universitas Gresik, 2017)
In this chance, the writer intends to analyze a process of search for identity in a novel by Nancy Friday entitled My Mother/My Self. The writer chooses it for containing an attractive story about search for identity. Specifically the objectives of the study entitled Search for Identity in NancyÃ¢â‚¬â„¢s Character in Nancy FridayÃ¢â‚¬â„¢s My Mother/My Self are: (1) to describe how Nancy as the main female character in My Mother/My Self search for identity, (2) to elaborate the influences of NancyÃ¢â‚¬â„¢s mother in NancyÃ¢â‚¬â„¢s search for identity, (3) to explain the results of NancyÃ¢â‚¬â„¢s search for identity. The research approach that is applied in this study is psychological approach. It is used in order to analyze the psychological types that is the process of search for identity experienced by Nancy within this novel. Meanwhile the research methodology consists of three things. In the data collection, the writer employs library research and internet browsing. The writer uses the theories that relate to the search for identity, the ways to search for identity, the influences of mother, the result, etc. Those theories become the base in analyzing the data found in this novel. Then the data corpus consists of words, clauses, dialogue, etc that refer to the search for identity in Nancy FridayÃ¢â‚¬â„¢s My Mother/My Self. Afterwards, to analyze the data, the writer uses content analysis which emphasizing the data that is in form of texts. After analyzing the data, the writer finds that Nancy searches for identity because she wants to change the pattern which regards that a daughter will be same with her mother mostly in her lifeÃ¢â‚¬â„¢s aspect. Then Nancy searches for identity through family relation, status symbols, Ã¢â‚¬Å“grown-upÃ¢â‚¬Â behavior, rebellion and idols or models. The writer also finds that NancyÃ¢â‚¬â„¢s mother influences Nancy in attitude and personality through her terrible anxieties and fear. She also influences Nancy in ethical and moral values by being careless and introvert. Meanwhile Nancy in fact can manage the process well. She finally achieves her identity by being independent and different from her mother. She also can make better relationship with her mother. Then based on the finding, the writer can conclude that Nancy searches for her identity through some ways. During the process, her mother takes significant role and in the end Nancy can get the positive results such the identity itself